PENGARUH PAJAK BUMI DAN BANGUNAN TERHADAP PENDAPATAN ASLI DAERAH (PAD) PADA PEMERINTAH KABUPATEN CIAMIS PERIODE 2018-2020 - Rukmi Juwita; Khairaningrum Mulyanti; Fathur Ainur Rahmaan (JAMER : Jurnal Akuntansi Merdeka, 2022)
Earth and Building Tax is a tax on earth and/or buildings owned, controlled, and/or utilized by private persons or entities, except for acreage used for plantation, forestry, and mining business activities. Local revenue is income obtained from the local tax sector, local levies generated from regionally owned business entities, the results of the management of separated regional wealth, and other legitimate local income. The tax potential of the earth and buildings is very potential. Still, its utilization has not been optimal because of the lack of public awareness of paying taxes. The equipment responsible for processing needs to be improved, such as the collection of tax objects and tax subjects with down. Direct and review in the field so that the receipt and tax revenue of Earth and Building are more effective so that people's lives can be guaranteed. The purpose of this study was to find out how the Earth and Building Tax affects Local Native Income on the Ciamis Regency government. This type of research is quantitative research. Use secondary data sources. Hypotheses are determined using one-party (one-sided) tests. The analytical techniques used are product-moment correlation, simple linear regression analysis, determination coefficient analysis, and t-test. The results showed that the income of earth and building taxes on Regional Original Income (PAD) in the Ciamis Regency Government had a powerful relationship with a correlation rate of 0.986. While the coefficient of determination (r2) = 0.972 or 97.2% with a sig value of 0.000 < 0.05. This means that the value of thitung is greater than the ttabel, so it can be concluded that the proposed hypothesis is accepted that there is a significant influence between the Earth and Building Tax on Original Local Income on the Ciamis Regency Government".